Bibliometric Analysis of Social Sciences - Tessa Simahate; Donni Yudha Prawira; Siti Nurbaidah; Elsya Fitri Utami; Cut Lidya Mutia (Universitas Negeri Medan, 2022)
This study aims to determine the outcomes of research conducted by students in the Faculty of Social Sciences between the academic years of 2018 and 2020, as well as the suitability of those results, which includes: the scientific field studied, what topics are saturated and no longer in demand, and the trend of topic distribution growing. At this study, the Deway Decimal Classification (DDC) standard was used to map out the distribution of research fields among students in the Faculty of Social Sciences. In order to develop the roadmap for each study program at the Faculty of Social Sciences, State University of Medan for the upcoming student research, this research combines quantitative and qualitative methods to determine the distribution of thesis research topics. The thesis sample data obtained from the Medan State University Repository was processed using the VosViewer program by means of the data first tabulated with the help of M.S. Excel and the Open Refine Application then analyzed descriptively qualitatively. According to the study's findings, Medan State University's Faculty of Social Sciences will have graduated 1,341 theses between 2018 and 2020 consisting of the History Education Study Program, Geography Education, Anthropology Education and Civics Education. According to data from a mapping of scientific fields based on DDC that depicts the research areas of each study program in the Faculty of Social Sciences, education, research, related historical topics, geography education, national and ethnic groups, and citizenship and related topics are the ones that students are most interested in researching.